New Therapeutic Concept of NAD Redox Balance for Cisplatin Nephrotoxicity - Oh, Gi-Su (Biomed Res Int, 2016)
Cisplatin is a widely used chemotherapeutic agent for the treatment of various tumors. In addition to its antitumor activity, cisplatin affects normal cells and may induce adverse effects such as ototoxicity, nephrotoxicity, and peripheral neuropathy. Various mechanisms such as DNA adduct formation, mitochondrial dysfunction, oxidative stress, and inflammatory responses are closely associated with cisplatin-induced nephrotoxicity; however, the precise mechanism remains unclear. The cofactor nicotinamide adenine dinucleotide (NAD(+)) has emerged as a key regulator of cellular energy metabolism and homeostasis. Recent studies have demonstrated associations between disturbance in intracellular NAD(+) levels and clinical progression of various diseases through the production of reactive oxygen species and inflammation. Furthermore, we demonstrated that reduction of the intracellular NAD(+)/NADH ratio is critically involved in cisplatin-induced kidney damage through inflammation and oxidative stress and that increase of the cellular NAD(+)/NADH ratio suppresses cisplatin-induced kidney damage by modulation of potential damage mediators such as oxidative stress and inflammatory responses. In this review, we describe the role of NAD(+) metabolism in cisplatin-induced nephrotoxicity and discuss a potential strategy for the prevention or treatment of cisplatin-induced adverse effects with a particular focus on NAD(+)-dependent cellular pathways.